The Linkages of Laboratory Facilities and Motivation to the Learning Outcomes of Semarang High School Students (Universitas Negeri Semarang, 2019)
Biology as part of natural science is a collection of concepts-principles-theory (science product) where in there are a number of scientific values and properties. Therefore, biology learning must be carried out according to the method of work or scientific method in order to produce scientific products. Practicum activities carried out in learning are a scientific process that can make students do analytic thinking to understand science products. Motivation possessed by students in each learning activity is very instrumental in improving student. This study aims to determine the relationship between laboratory facilities and motivation for learning outcomes of high school students. This study has three variables: Variables (X1) is motivation, variables (X2) is laboratory facilities and variable (Y) is the student learning outcomes. this study was conducted using correlational quantitative method, the model used was the documentation method which aims to obtain data from student learning achievement, the data then analyzed using multiple regression analysis with the help of SPSS for windows release 20.The results of the study are as follow contribution of variables X1 and X2 (laboratory facilities and motivation) to variable Y (student learning outcomes) that is 59 % and the level of correlation is quite strong.